Percepção de um grupo de agricultores da localidade de São João do município de Marapanim-PA, sobre o método de corte e trituração como alternativa ao método tradicional de corte e queima da vegetação secundária - SANTOS, Loraine de Oliveira Lauris dos (Universidade Federal do Pará, 2021)
Farming production systems are in continuous changing, and constantly new exploration techniques arise, affecting the natural resources and modifying the planted media. The impact of a new production system technology may interfere in the agricultors’ knowledge acquired and transmitted through generations. The purpose of this work is to evaluate the aspects of a technical change from traditional cultivation system (slash and burn) to the fire-free system experienced by the small farmers of Community São João (Pará’s